A PVC material and its preparation method and application

By adding zinc-based flame retardant and flame retardant high-temperature toughening powder to PVC materials and combining them, the problems of insufficient flame retardant and smoke resistance and impact resistance of existing PVC materials are solved, and the effects of high oxygen index and low smoke density are achieved, meeting national standards.

CN117683304BActive Publication Date: 2025-03-14LIANSU TECH DEV WUHAN
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311469722.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2025-03-14
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

Existing PVC materials have shortcomings in flame retardant and smoke suppression and impact resistance, especially their low oxygen index and high smoke density, which are difficult to meet national standards.

Method used

By adding zinc-based flame retardant and flame retardant high-temperature toughening powder and combining it within a certain mass ratio, the flame retardant and smoke suppression effect and impact resistance of PVC materials are improved.

Benefits of technology

The high flame retardant insulation performance of PVC materials was achieved, the oxygen index reached 37.4%, the smoke density was only 40.6, which met the national standard of GB/T 1614-2000, and improved the mechanical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005131713190000061
    Figure GDA0005131713190000061
Patent Text Reader

Abstract

The present invention discloses a PVC material and a preparation method and application thereof, and specifically relates to the technical field of chemical building materials. A PVC material is composed of the following components by mass: 100 parts of polyvinyl chloride resin, 5 to 20 parts of flame retardant and high temperature toughening powder, 2 to 8 parts of zinc flame retardant, 2 to 8 parts of impact modifier, and 8.5 to 35 parts of other additives. The present invention adds zinc flame retardant and flame retardant and high temperature toughening powder for compounding, and the oxygen index of the prepared PVC material reaches 37.4%, the smoke density is only 40.6, and it has good mechanical properties and flame retardant and smoke suppression properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical building materials, and in particular to a PVC material and a preparation method and application thereof. Background Art

[0002] Polyvinyl chloride (PVC) is widely used in electrical insulation materials, water supply and drainage pipes, door and window profiles and other fields due to its good chemical stability, flame retardancy and self-extinguishing properties, and high insulation properties. It is one of the most widely used general-purpose plastics. In the past, people have always regarded PVC as a flame retardant material, but this is not the case. In order to facilitate processing in industry, various processing aids, plasticizers and other auxiliary processing are added to the PVC plastic system, which will reduce the performance of PVC and reduce the mechanical properties and flame retardant properties of its products. Therefore, it is of great significance to improve the compatibility and flame retardant properties of materials with PVC.

[0003] Flame retardants can be divided into two categories: inorganic flame retardants and organic flame retardants according to their components. There are many varieties of organic flame retardants, which are mainly divided into two categories: phosphorus-based and halogen-based flame retardants according to the type of compound. However, halogen flame retardants produce toxic smoke during combustion and are used less and less. Red phosphorus, as a commonly used phosphorus-based flame retardant, is prone to explosion during use. Long-term contact with air will release highly toxic PH3 gas, and it is easy to absorb water and has poor compatibility with polymers. The problem with inorganic flame retardants is that only a large amount can achieve a flame retardant effect, and inorganic flame retardants have low bonding strength with polymers and poor compatibility. Adding a large amount will lead to a decrease in the mechanical properties of plastics.

[0004] The prior art discloses a B2-level low-smoke, low-halogen flame-retardant PVC cable material and its preparation process, which comprises the following raw materials: 90-110 parts of polyvinyl chloride resin, 35-45 parts of plasticizer, 55-60 parts of magnesium hydroxide, 3-5 parts of stabilizer, 8-12 parts of flame retardant, 10-12 parts of smoke suppressant, 2-3 parts of antioxidant and 1-2 parts of dye, wherein the flame retardant is an environmentally friendly zinc borate flame retardant. The prior art achieves a certain flame retardant and smoke suppression effect by adding flame retardant and smoke suppressant, but the oxygen index of the prepared PVC material is only 34%. Summary of the invention

[0005] In order to improve the flame retardant, smoke suppression effect and impact resistance of PVC materials in the prior art, the present invention provides a PVC material, which improves the flame retardant, smoke suppression effect and impact resistance of the PVC material by adding a zinc-based flame retardant and a flame retardant high-temperature toughening powder for compounding.

[0006] Another object of the present invention is to provide a method for preparing a PVC material.

[0007] Another object of the present invention is to provide an application of PVC material in a highly flame-retardant insulating wire duct.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A PVC material is composed of the following components by mass:

[0010] 100 parts of polyvinyl chloride resin, 5-20 parts of flame retardant high temperature toughening powder, 2-8 parts of zinc flame retardant, 2-8 parts of impact modifier, and 8.5-35 parts of other additives.

[0011] The flame retardant high temperature toughening powder is a micro-nano powder with a stable crystal structure and a gold particle size. It is easy to disperse and bind with the resin. After being doped and dispersed with the polyvinyl chloride resin, it can induce a reaction with the free radicals in the polyvinyl chloride resin and the inorganic substances in the formula of the present invention in a flame environment or under high temperature for a short time in seconds, and can simultaneously bond with the metal substances in the zinc flame retardant and other additives (heat stabilizers) to form a high-hardness, wear-resistant, high-adhesion and micro-network chain structure composite material "membrane wall structure layer". The network chain structure composite material "membrane wall structure layer" is a three-dimensional network structure, and the metal substance in the formula is bonded in the middle as a reinforcing fulcrum, thereby improving the impact resistance of the material. It also has a synergistic flame retardant effect, effectively compensating for the fire conditions during the combustion of organic resins and the defects in high temperature environments.

[0012] Zinc flame retardants can effectively catalyze the dehydrochlorination reaction in PVC materials. HCl gas can play a flame retardant role in the gas phase. At the same time, zinc flame retardants can react with HCl to form ZnCl2. ZnCl2, as a strong Lewis acid, can effectively catalyze the dehydrochlorination of PVC to form trans-polyene substances, prevent the formation of polycyclic benzene ring compounds after dehydrochlorination of PVC, promote the cross-linking and carbonization of the carbon skeleton, and make it difficult to volatilize into the gas phase, thereby reducing the generation of benzene when the material burns. Benzene will produce a lot of thick smoke when it burns, so reducing the generation of benzene can achieve the effect of smoke suppression.

[0013] The compound use of flame retardant high temperature toughening powder and zinc flame retardant makes the catalytic de-HCl effect of zinc flame retardant and the flame retardant high temperature toughening powder induce the formation of micro-network chain structure composite material "membrane wall structure layer" in seconds. The two promote each other, which is beneficial to the early cross-linking and carbonization of PVC and plays a synergistic flame retardant effect. The compound use of zinc flame retardant and flame retardant high temperature toughening powder can improve the flame retardant and smoke suppression properties of PVC materials. There is a synergistic effect between flame retardant high temperature toughening powder and zinc flame retardant.

[0014] Preferably, the mass ratio of the flame retardant high temperature toughening powder to the zinc flame retardant is (2-6):1.

[0015] Under the mass ratio of flame retardant high temperature toughening powder to zinc flame retardant specified in the present invention, the synergistic effect of the two can be better exerted. With the addition of flame retardant high temperature toughening powder, the limiting oxygen index (LOI) value of PVC material, that is, the flame retardant performance of the material, can be improved. However, with the increase of the amount of flame retardant high temperature toughening powder added, the LOI increases slowly, indicating that the flame retardant high temperature toughening powder has a certain flame retardant effect on PVC, but its flame retardant efficiency is not high. With the increase of zinc flame retardant, the LOI value and residual carbon rate of PVC sample (the higher the residual carbon rate, the better the flame retardant performance) are more significantly improved than those with the single addition of flame retardant high temperature toughening powder. However, with the increase of the amount of zinc flame retardant added, exceeding the range specified in the present invention, the LOI value and the residual carbon rate decrease instead. When the content of zinc flame retardant is large and is not within the range specified in the present invention, it has no obvious effect on the flame retardant and smoke suppression performance of the material, and may even reduce the residual carbon rate of the material.

[0016] Preferably, the particle size of the flame retardant high temperature toughening powder is 0.01-45 μm.

[0017] Micron-sized powder can be better dispersed evenly with other materials, improve the compatibility of the matrix, and thus maintain the mechanical properties of the product. If the particle size of the flame-retardant and high-temperature toughening powder is too large, the compatibility with the matrix is ​​poor, which will seriously affect the mechanical properties of the matrix. If the particle size of the flame-retardant and high-temperature toughening powder is too small, it is easy to adhere to the feed port during production, affecting the production speed and efficiency.

[0018] More preferably, the particle size of the flame retardant high temperature toughening powder is 20 to 30 μm.

[0019] Within this particle size range, the flame retardant and high temperature toughening powder can be better compatible with the matrix material, thereby improving the mechanical properties and flame retardant and smoke suppression properties of the PVC material.

[0020] Preferably, the crystal structure of the flame retardant high temperature toughening powder is a spinel structure.

[0021] The spinel structure has high thermal stability, mechanical heat resistance and catalytic carbonization performance, which can better improve the flame retardant properties of the material.

[0022] Preferably, the flame retardant high temperature toughening powder includes PGT360 and / or PGT460.

[0023] PGT360 and PGT460 are nano-scale powders that are easy to disperse. During the material combustion process or in the temperature range of 380-660°C, they can provide high-temperature oxygen isolation and bonding for the reaction, achieving flame retardancy, drip-free, non-powdering, high hardness, wear resistance, corrosion resistance and antioxidant functions, effectively making up for the fire conditions during the combustion of organic resins and the defects in high-temperature environments; flame retardant and high-temperature toughening powders have a lower cost, and through a new combination of formulas, they can replace expensive imported brand products and reduce production costs; flame retardant and high-temperature toughening powders are halogen-free, and there is no smoke after combustion, no heavy metals and controlled components, are environmentally friendly, and can meet relevant national and European, American and Japanese standards.

[0024] Preferably, the zinc-based flame retardant is one or more of zinc aluminate, zinc oxide, and zinc borate.

[0025] Within the limited scope of the present invention, the less the amount of zinc-based flame retardant added, the better its flame retardant properties. It can be used in combination with other flame retardants (the present invention is flame retardant high-temperature toughening powder) to utilize the synergistic effect between flame retardants to improve the flame retardant, smoke suppression and mechanical properties of the material.

[0026] Preferably, the impact modifier is one or more of chlorinated polyethylene (CPE), acrylic polymer (ACR) and methyl methacrylate-butadiene-styrene terpolymer (MBS).

[0027] Impact modifiers can better promote the plasticizing ability of the formula and improve the impact resistance of the product.

[0028] In a specific embodiment of the present invention, other additives include 5 to 20 parts of light calcium carbonate, 2 to 6 parts of heat stabilizer, 0.5 to 3 parts of processing aid, 0.5 to 3 parts of lubricant, and 0.5 to 3 parts of pigment.

[0029] Specifically, the processing aid is a methyl methacrylate-acrylate graft polymer.

[0030] Preferably, the sedimentation volume of light calcium carbonate is ≥2.5 mL / g and the whiteness is ≥90.

[0031] The present invention performs sedimentation volume and whiteness tests on calcium carbonate in accordance with HG / T 2226-2019. Among them, the sedimentation volume test process is to weigh 10g of the sample, place it in a stoppered measuring cylinder filled with 30ml of water, add water to 100ml, shake it up and down for 3min, and then stand it at room temperature for 3h, record the volume occupied by the sediment, and the obtained sedimentation volume is calculated as the volume occupied by each gram of sediment; the whiteness test process is to prepare the sample into a sample with a smooth surface, place it in a whiteness meter, and test to obtain the sample whiteness value. Different calcium carbonate usage scenarios have different requirements for the sedimentation volume and whiteness of calcium carbonate. The sedimentation volume and whiteness defined in the present invention are requirements for the use of light calcium carbonate on plastics.

[0032] Preferably, the heat stabilizer is one or more of a calcium zinc stabilizer, a composite lead salt stabilizer and an organic tin stabilizer.

[0033] Preferably, the lubricant is one or more of paraffin wax, polyethylene wax (PE wax), stearic acid and chlorinated polyethylene wax (CPE wax).

[0034] Preferably, the pigment is titanium dioxide.

[0035] The present invention also protects a method for preparing a PVC material, comprising the following steps:

[0036] The polyvinyl chloride resin, flame retardant high temperature toughening powder, zinc flame retardant, impact modifier and other additives are heated and stirred to mix evenly, and then heated and plasticized and extruded after cooling.

[0037] In a specific embodiment of the present invention, the heating, stirring and mixing can be carried out in a hot mixing cylinder of a high-speed mixer. When the temperature reaches 110-120°C, the materials are discharged into a cold mixing cylinder for stirring and cooling to 30-40°C. The heating and plasticizing can be carried out in an extruder, and the extrusion temperature can be 150-200°C.

[0038] The invention also protects application of a PVC material in a highly flame-retardant insulating wire duct.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The invention uses a flame retardant high temperature toughening powder and a zinc flame retardant in a certain mass ratio range, so that the prepared PVC material has good mechanical properties and flame retardant and smoke suppression properties. Specifically, the prepared PVC material can meet the national standard GB / T 1614-2000, and its oxygen index reaches 37.4%, and the smoke density is only 40.6, and has good mechanical properties and flame retardant and smoke suppression properties. DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art, and the reagents and materials used in the following examples are all commercially available.

[0042] Polyvinyl chloride: SG-5 type PVC resin, purchased from Xinjiang Zhongtai Chemical Co., Ltd.;

[0043] Flame retardant high temperature toughening powder a: PGT360, purchased from Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.;

[0044] Flame retardant high temperature toughening powder b: PGT460, purchased from Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.;

[0045] Ordinary flame retardant high temperature powder: flame retardant masterbatch, Zhengzhou Boxuan Flame Retardant Technology Co., Ltd.;

[0046] Zinc flame retardant: zinc oxide, Tianjin Chemical Reagent Factory;

[0047] Tin flame retardant: zinc stannate ZnSnO3, purchased from Hubei Chengfeng Chemical Co., Ltd.;

[0048] Impact modifier: chlorinated polyvinyl chloride (CPE), 135A, Shandong Riko Chemical Co., Ltd.;

[0049] Light calcium carbonate: Jinshan light calcium carbonate, model PCC-P, Guilin Jinshan New Materials Co., Ltd.

[0050] Heat stabilizer: calcium zinc stabilizer, model 161FP, Baerlocher Plastic Additives (Jiangsu) Co., Ltd.;

[0051] Processing aid: methyl methacrylate-acrylate graft polymer, model LPA-40, Shandong Ruifeng Polymer Materials Co., Ltd.;

[0052] Lubricant: PE wax, model YT-95L, Inner Mongolia Yuanji Chemical Co., Ltd.;

[0053] Pigment: Titanium dioxide, model NR-950, Nanjing Titanium Dioxide Chemical Co., Ltd.

[0054] Embodiments 1 to 4

[0055] A PVC material, the composition of raw materials by weight is shown in Table 1.

[0056] The particle sizes of the flame retardant high temperature toughening powder a and the flame retardant high temperature toughening powder b are both 25 μm, and the crystal structures are both spinel structures.

[0057] The method for preparing the PVC material in the above-mentioned embodiments 1 to 4 comprises the following steps:

[0058] The polyvinyl chloride resin, flame retardant high temperature toughening powder a or flame retardant high temperature toughening powder b, zinc flame retardant, impact modifier and other additives are heated, stirred and mixed, and then extruded after plasticization to obtain PVC material.

[0059] The raw materials are put into the hot mixing cylinder of the high-speed mixing unit, and after the high-speed stirring is started, when the temperature of the hot mixing cylinder reaches 120°C, the materials are discharged into the cold mixing cylinder for stirring and cooling, and when the temperature drops to 40°C, the materials are put into the conical twin-screw extruder for plasticization and molding. The temperature of the extruder is set to 160-195°C, and the molding temperature is set to 150-200°C.

[0060] Example 5

[0061] A PVC material, the composition of raw materials by weight is shown in Table 1, and the difference from Example 1 is that the particle size of the flame retardant high temperature toughening powder a is 0.01 μm.

[0062] The preparation method of the PVC material in the above-mentioned embodiment 5 is the same as that in embodiment 1.

[0063] Example 6

[0064] A PVC material, the composition of raw materials by weight is shown in Table 1, and the difference from Example 1 is that the particle size of the flame retardant high temperature toughening powder a is 45 μm.

[0065] The preparation method of the PVC material in the above-mentioned embodiment 6 is the same as that in embodiment 1.

[0066] Table 1

[0067]

[0068] Comparative Example 1

[0069] A PVC material, the raw material mass fraction composition is different from that of Example 1 in that: the flame retardant high temperature toughening powder a is replaced by ordinary flame retardant high temperature powder.

[0070] The preparation method of the PVC material in the above comparative example 1 is the same as that in example 1.

[0071] Comparative Example 2

[0072] A PVC material, the composition of raw materials by mass fraction is different from that of Example 1 in that the zinc-based flame retardant is replaced by a tin-based flame retardant (zinc stannate ZnSnO3).

[0073] The preparation method of the PVC material in the above comparative example 1 is the same as that in example 1.

[0074] Comparative Example 3

[0075] A PVC material, the raw material composition by mass is different from that in Example 1 in that: the flame retardant high temperature toughening powder a is 45 parts, the zinc flame retardant is 3 parts, and the mass ratio of the flame retardant high temperature toughening powder a to the zinc flame retardant is 15:1.

[0076] The preparation method of the PVC material in the above comparative example 3 is the same as that in example 1.

[0077] Test example performance measurement

[0078] (1) Impact performance test: According to GB / T 1614-2000, the test standard is: no visible breakage and cracks are qualified, indicating that the material has good impact resistance.

[0079] (2) Oxygen index determination. According to GB / T 1614-2000, the test standard is: OI ≥ 32%. The larger the OI value, the larger the oxygen index, which means the better the flame retardant effect of the material.

[0080] (3) Smoke density measurement. According to GB / T 1614-2000, the test standard is SDR ≤ 75. The smaller the SDR value, the smaller the smoke density, which means the better the smoke suppression effect of the material.

[0081] The performance tests of Examples 1 to 6 of the present invention and Comparative Examples 1 to 3 are shown in Tables 2 and 3.

[0082] Table 2 Performance measurement results of Examples 1 to 6

[0083] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Impact performance 50 / 50 no break 50 / 50 no break 50 / 50 no break 50 / 50 no break 50 / 50 no break 50 / 50 no break Oxygen index / % 37.4 36.8 36.1 35.7 36.3 35.2 Smoke density 40.6 42.7 48.5 45.2 51.4 53.7

[0084] Table 3 Performance measurement results of comparative examples 1 to 3

[0085] Comparative Example 1 Comparative Example 2 Comparative Example 3 Impact performance 42 / 50 no damage 50 / 50 no break 45 / 50 no damage Oxygen index / % 32.8 32.6 31.7 Smoke density 75.6 80.1 78.2

[0086] It can be seen from Table 2 that the flame retardant insulating PVC materials obtained in Examples 1 to 6 were tested in accordance with GB / T1614-2000 "Flame-retardant Insulated Polyvinyl Chloride Wire Trays and Accessories". The results showed that the impact samples in each embodiment had no breakage or visible cracks. In Example 1 and Example 2, when the particle size of the flame retardant high-temperature toughening powder was 25 μm and the mass ratio of the flame retardant high-temperature toughening powder to the zinc flame retardant was 3.63:1, they had the best flame retardant and smoke suppression performance, and their oxygen index was greater than that of the other embodiments, and the smoke density was less than that of the other embodiments; it can be seen from Example 3 and Example 4 that when the mass ratio of the flame retardant high-temperature toughening powder to the zinc flame retardant was in the range of (2 to 6): 1, the flame retardant and smoke suppression effect was better; Examples 5 and 6 were to change the particle size of the flame retardant high-temperature toughening powder. From the results of the examples, it can be seen that the flame retardant high-temperature toughening powder has a good flame retardant and smoke suppression effect in the range of 0.01 to 45 μm. The oxygen index of the PVC material in the embodiment of the present invention is greater than 35.2%, meeting the requirement of oxygen index OI ≥ 32%, the smoke density SDR is much less than 75, only 53.7, the flame retardant and insulating properties fully meet the national standard requirements, and have good mechanical properties and flame retardant and smoke suppression effects.

[0087] It can be seen from Table 3 that in Comparative Example 1, ordinary flame retardant and high temperature toughening powder is used, and its impact performance is worse than that of the embodiment, and its mechanical properties are not as good as the effect of the specific flame retardant and high temperature toughening powder used in the present invention, and its smoke density does not meet the requirements of national standards; in Comparative Example 2, a tin-based flame retardant is used, and although it has certain mechanical properties, its smoke density does not meet the requirements of national standards; the mass ratio of the flame retardant and high temperature toughening powder to the zinc-based flame retardant in Comparative Example 3 is not within the limited range of the present invention, and the mechanical properties of the prepared PVC material are poor, and the oxygen index and smoke density do not meet the requirements of national standards.

[0088] The data results of the embodiments and comparative examples show that when the flame retardant and high temperature toughening powder used is not the flame retardant and high temperature toughening powder a / b material of the present invention, the flame retardant used is not a zinc-based flame retardant, and the mass ratio (proportion) of the flame retardant and high temperature toughening powder to the zinc-based flame retardant is not within the range defined by the present invention, the prepared PVC material cannot simultaneously meet the requirements of having a higher oxygen index, a lower smoke density and better impact mechanical properties.

[0089] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A PVC material, characterized in that: The PVC material is composed of the following components in parts by mass: 100 parts of polyvinyl chloride resin, 5-20 parts of flame retardant high temperature toughening powder, 2-8 parts of zinc flame retardant, 2-8 parts of impact modifier, and 8.5-35 parts of other additives; The mass ratio of the flame retardant high temperature toughening powder to the zinc flame retardant is (2-6):1; The particle size of the flame retardant high temperature toughening powder is 20 to 30 μm.

2. The PVC material according to claim 1, characterized in that: The crystal structure of the flame retardant high temperature toughening powder is a spinel structure.

3. The PVC material according to claim 1, characterized in that: The flame retardant high temperature toughening powder includes PGT360 and / or PGT460.

4. The PVC material according to claim 1, characterized in that: The zinc-based flame retardant is one or more of zinc aluminate, zinc oxide, and zinc borate.

5. The PVC material according to claim 1, characterized in that: The impact modifier is one or more of chlorinated polyethylene, acrylic polymer and methyl methacrylate-butadiene-styrene terpolymer.

6. A method for preparing the PVC material according to any one of claims 1 to 5, characterized in that: The steps include: The polyvinyl chloride resin, flame retardant high temperature toughening powder, zinc flame retardant, impact modifier and other additives are heated and stirred to mix evenly, and then heated and plasticized and extruded after cooling.

7. Use of the PVC material according to any one of claims 1 to 5 in highly flame-retardant insulating wire ducts.

Citation Information

Patent Citations

  • Flame-retardant smoke-suppressing PVC wire way and preparation method thereof

    CN105038026A